Photocatalytic Anaerobic Oxidation of Aromatic Alcohols Coupled With H2 Production Over CsPbBr3/GO-Pt Catalysts - Taoran Chen; Mengqing Li; Lijuan Shen; Maarten B. J. Roeffaers; Bo Weng; Haixia Zhu; Zhihui Chen; Dan Yu; Xiaoyang Pan; Min-Quan Yang; Qingrong Qian (Frontiers in Chemistry, 2022)
Metal halide perovskites (MHPs) have been widely investigated for various photocatalytic applications. However, the dual-functional reaction system integrated selective organic oxidation with H2 production over MHPs is rarely reported. Here, we demonstrate for the first time the selective oxidation of aromatic alcohols to aldehydes integrated with hydrogen (H2) evolution over Pt-decorated CsPbBr3. Especially, the functionalization of CsPbBr3 with graphene oxide (GO) further improves the photoactivity of the perovskite catalyst. The optimal amount of CsPbBr3/GO-Pt exhibits an H2 evolution rate of 1,060 μmol g−1 h−1 along with high selectivity (>99%) for benzyl aldehyde generation (1,050 μmol g−1 h−1) under visible light (λ > 400 nm), which is about five times higher than the CsPbBr3-Pt sample. The enhanced activity has been ascribed to two effects induced by the introduction of GO: 1) GO displays a structure-directing role, decreasing the particle size of CsPbBr3 and 2) GO and Pt act as electron reservoirs, extracting the photogenerated electrons and prohibiting the recombination of the electron–hole pairs. This study opens new avenues to utilize metal halide perovskites as dual-functional photocatalysts to perform selective organic transformations and solar fuel production.